Factors Associated with the Acceptance of COVID-19 Vaccines in Citizens of Northern Peru: Cross-Sectional Study - Yupari-Azabache IL; Díaz-Ortega JL; Bardales-Aguirre LB; Barros-Sevillano S; Paredes-Díaz SE (Dove Medical Press, 2022)
Irma Luz Yupari-Azabache,1 Jorge Luis Díaz-Ortega,1,2 Lucia Beatriz Bardales-Aguirre,3 Shamir Barros-Sevillano,1,4 Susana Edita Paredes-Díaz1 1Grupo de Investigación en Enfermedades Infecciosas y Transmisibles, Universidad César Vallejo, Trujillo, Peru; 2Escuela Profesional de Nutrición, Universidad Cesar Vallejo, Trujillo, Peru; 3Departamento de Ciencias, Universidad Privada del Norte, Trujillo, Peru; 4Sociedad Científica de Estudiantes de Medicina de la Universidad César Vallejo, Trujillo, PeruCorrespondence: Irma Luz Yupari-Azabache, Grupo de Investigación en Enfermedades Infecciosas y Transmisibles, Universidad César Vallejo, Av. Larco 1770, Trujillo, Peru, Tel +51 964612831, Email IYUPARI@ucv.edu.pePurpose: The presence of the COVID-19 coronavirus in Peru, and especially in northern Peru, was very fast and caused many deaths. As a result, vaccination proved to be the most immediate option to control it. However, a sector of the population was reluctant to vaccination. Therefore, this study aimed to analyze the factors associated with the acceptance of COVID-19 vaccines by citizens of northern Peru.Patients and Methods: The study was observational, descriptive-correlational and the sample was stratified and consisted of 516 citizens from eight departments of northern Peru, who answered an online questionnaire regarding sociodemographic, cultural and health aspects. The data were analyzed using statistical tests of association and a logistic model was estimated to identify factors predicting vaccine acceptance.Results: Among the factors associated with vaccine acceptance, sociodemographic factors such as age and family income, cultural factors such as level of knowledge, and health factors such as having another chronic disease and a vaccine with a higher confidence (p< 0.05) were found. In addition, 12% of the population do not trust them, 10% are afraid that they may cause thrombosis, 13% disagree with vaccination for children, 7% think that a chip will be implanted and 8% believe that their DNA will be changed. However, most people accept vaccination and consider it necessary. A multivariate analysis was also performed for the acceptance of vaccines, which presented a percentage of 80.2% correct in the prognosis.Conclusion: The multivariate analysis allowed a conclusion that the predictor variables for vaccine acceptance are household income of less than 1000 Peruvian soles per month, low or medium levels of knowledge, and having another chronic disease.Keywords: COVID-19, vaccination, Peru, pandemic